Synthesis and characterization of silver/talc nanocomposites using the wet chemical reduction method - Shameli, Kamyar; Ahmad @ Ayob, Mansor; Wan Yunus, Wan Md. Zin; Ibrahim, Nor Azowa; Darroudi, Majid (Dove Medical Press Ltd., 2010)
In this study, silver nanoparticles (Ag-NPs) were synthesized using the wet chemical reduction method on the external surface layer of talc mineral as a solid support. Silver nitrate and sodium borohydride were used as the silver precursor and reducing agent in talc. The talc was suspended in aqueous AgNO3 solution. After the absorption of Ag+ on the surface, the ions were reduced with NaBH4. The interlamellar space limits were without many changes (ds = 9.34–9.19 Aº); therefore, Ag-NPs formed on the exterior surface of talc, with dave = 7.60–13.11 nm in diameter. The properties of Ag/talc nanocomposites (Ag/talc-NCs)and the diameters of the Ag-NPs prepared in this way depended on the primary AgNO3 concentration. The prepared Ag-NPs were characterized by ultraviolet-visible spectroscopy,powder X-ray diffraction, transmission electron microscopy, scanning electron microscopy, and Fourier transform infrared. These Ag/talc-NCs may have potential applications in the chemical and biological industries.